80th IFLA General Conference and Assembly Lyon, France 16-22 August 2014 (Journal of EAHIL, 2017)
The theme of this year’s IFLA Conference, held in Lyon between 16 – 22 August, was Libraries, Citizens, Societies:Confluence for Knowledge. I hadn’t thought about its full significance until I arrived in Lyon, the second largest city inFrance after Paris, situated, indeed, at the confluence of two of the largest French rivers: the Rhone and the Saone. Theplace that inspired such a generous theme proved to be not only an excellent venue for the Conference, but it also charmedeveryone with its majestic views over the two rivers, its architecture and beautiful parks, its museums and history goingback to the ancient times, and, not least, the warm and stylish hospitality of its people.